Protection of Historical and Cultural Monuments: An Analysis of The Legislative Framework - Ursu, Viorica; Stamati, Mihaela (Technium Social Sciences Journal, 2022)
The dynamics in which changes occur in society require the state and citizens to face a wide range of problems of devaluation of historical and cultural monuments. Safeguarding the monuments of history and culture does not allow us to incubate the most representative values ​​of our past. In the end, does not unite as a national identity and has us as a nation. These cultural goods are also considered actual files of the cultural heritage of all humanity, and the elaboration of explicit and necessary normative acts has become a norm on the agenda. The analysis of the international and national legislative framework in protecting historical and cultural monuments is subject to analysis in presenting the work as a legal and social phenomenon with many perspectives. Therefore, research is essential from all points of view: theoretically, scientifically, and practically. This analysis was carried out to identify the normative acts in this segment of cultural heritage protection, the decision-makers' applied mechanisms, the legislative gaps, or the normative dubbing. The research will analyse international acts, considered rights for national acts. Moreover, contain general objectives, principles, and criteria for evaluating and protecting historical and cultural monuments. Particular attention was also paid to national legislation to determine the system's effectiveness for protecting cultural heritage, particularly monuments of history and culture.